The Comparative Figure of Speech in a Poetry Collection entitled Ibu Menanak Nasi hingga Matang Usia Kami by Emi Suy - Wati, Maulida Laily Kusuma; Supriyanto, RM. Teguh; Baehaqie, Imam (Universitas Negeri Semarang, 2023)
This article discusses a stylistic study focusing on comparative figurative language in the collection of poems from Ibu Menanak Nasi hingga Matang Usia Kami Poetry by Emi Suy. The purpose of this study is to describe the form of a comparative figure of speech in the poetry anthology of Ibu Menanak Nasi hingga Matang Usia Kami Poetry. This study uses a stylistic approach. The source of the data in this study was the anthology of the poem Ibu Menanak Nasi hingga Matang Usia Kami Poetry by Emi Suy published in 2022. The data collection technique used the first level semiotic reading technique, namely heuristic reading. The data analysis technique uses the structuralism-semiotic method, the researcher uses the second level reading technique, namely the hermeneutic technique. The data examined in this poem is in the form of stanzas in the poem which will later be used to find out the use of figure of speech. The results of this study are that the researcher found the most dominant comparative figure of speech, namely: (1) metaphorical figure of speech with 7 data (2) simile figure of speech with 3 data (3) personification figure of speech with 2 data (4) allegory figure of speech with 3 data (5) alusio figure of speech with 2 data and (5) a figure of speech on tautology 2 data. This collection of poems uses a comparative figure of speech, a combination of metaphors and similes which become dominant in it so that the poems seem unfathomable, full of possibilities and full of ambiguity, connotations and metaphors are left in the poetry with the result that in the poem Ibu Menanak Nasi hingga Matang Usia Kami Poetry is felt to exhibit agility, agility, and fluency in playing Indonesian. Poetic suspense is scattered in several titles of these poems.